(3fXQjI GdEMJeGdGJ hGdJhRjYGJ GdEMJeGdjI (B:s (3fXQjI GdGMJeGdGJ h GdeJZjQGJ GdYThGFjI h OhGd JhRjYGJgG GdGMJeGdjI (B/s - (3ZjVGf,YHO GdMejO eMeO QHjYs ((3GdbGgQI(B: s (3OGQ GdcJH GdCcGOjejI(B, s, 2004)
(3fXQjI GdGMJeGdGJ , GdeJZjQGJ GdYThGFjI h OhGd GdJhRjY GdGMJeGdj , ebGjjS GdfRYI GdeQcRjI (B((3eYGde GdehVY(B) (3h GdJTJJ h GdYRhe , GdGfMOGQ h GdGQJHGW h GdGbJQGf , GdOhGd GdeejRI , JhRjYGJ OhGd aj eJZjQGJ YThGFjI h JMhjd GdeJZjQGJ (B.s
(3GdeQGLY U(B.779s
Keywords: (3GdEMJeGdGJs; (3GdEMUGA GdQjGVjs; (3GdQjGVjGJs